TINGKAT KESIAPAN E-LEARNING (E-LEARNING READINESS)UNIVERSITAS BINA DARMA SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN JARAK JAUH - Agustina, Merry; Bakti, Ahmad Mutatkin (JURNAL ILMIAH MATRIK, 2015)
Needs of Distance Education (ODL) can not escape from the cycle of communication and exchange of information among actors PJJ. This study aims to measure the level of readiness of e-Learning as a learning medium on the implementation of ODL. Measurement of e-Learning readiness is based on the model of the e-Learning readiness expressed by an index, which is mapped using the index e-Learning reediness version Aydin & Tasci with a scale of 1-5 based on variables faculty, students, staff and infrastructure. The study was conducted by using descriptive statistical techniques by using a questionnaire as an instrument of collecting data from 50 respondents consisting of 15 lecturers, 5 employees and 30 students. Results of data processing shows e-Learning UBD as PJJ media has an index of 4.3, which means ready to deploy an e-Learning (ready go).